PENGEMBANGAN METODE PENDUGAAN KEDALAMAN PERAIRAN DANGKAL MENGGUNAKAN DATA SATELIT SPOT-4. STUDI KASUS: TELUK RATAI, KABUPATEN PESAWARAN - Arief, Muchlisin; Hastuti, Maryani; Asriningrum, Wikanti; Parwati, Ety; Budiman, Syarif; Prayogo, Teguh (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2013)
Bathymetric estimation of shallow water depth using satellite remote sensing data becomes more prevalent. However, when these methods are implemented for areas with different environments, the results indicate the presence of irregularities. To minimize the deviation, conducted the merger of the information obtained from field measurements with reflectance values SPOT-4 satellite imagery. This paper proposed the method development for bathymetric estimation of shallow water depth based on the correlation function between the depth value of direct measurements using a "handheld echo-sounder" to the resultant of reflectance values (band 1 and band 3). The algorithm for bathymetric estimation of a shallow water depth consists of thresholding method and correlation functions. Threshold value (T) depth of 0.5 meters is determined from observations of the correlation function graph polynomial from five and magnitude is 0.35 <T <0.47. Based on the results of the calculations show that the SPOT-4 satellite data can be used to estimate the shallow water depths up to approximately 18 meters.